Willingness to Pay Farmers on Turmeric Extract to Reduce Health Impacts Due to Pesticide - Muslim, Azhari; Dadang, Dadang; Indrasti, Nastiti Siswi; Syaukat, Yusman (Universitas Ibn Khaldun Bogor, 2023)
Pesticide exposure has been shown to cause various diseases such as acute neurotoxicity, cardiovascular disease, cancer, allergies and nervous disorders. Economic assessment of the health costs of using pesticides is necessary to design effective policies and reduce poisoning in farming populations The herbal medicines used have the efficacy of preventing and treating chronic non-communicable diseases. The most widely consumed herbal medicine is turmeric. This study aimed to analyze the willingness to pay value of turmeric extract and the factors that influence the willingness to pay of turmeric extract. All shallot farmers have turmeric extract WTP as a herbal medicine to reduce the risk of pesticide poisoning. The average WTP of turmeric extract reaches IDR 625,777 per year.